The role of miR-152 in urological tumors: potential biomarkers and therapeutic targets - Li, Xin; Qian, Biao; Chen, Xu; Shen, Maolei; Zhao, Shankun (Frontiers in Immunology, 2024)
Urological malignant tumors pose a significant threat to human health, with a high incidence rate each year. Prostate cancer, bladder cancer, and renal cell carcinoma are among the most prevalent and extensively researched urological malignancies. Despite advancements in research, the prognosis for these tumors remains unfavorable due to late detection, postoperative recurrence, and treatment resistance. A thorough investigation into their pathogenesis is crucial for early diagnosis and treatment. Recent studies have highlighted the close association between microRNAs (miRNAs) and cancer progression. miRNAs are small non-coding RNAs composed of 19-23 nucleotides that regulate gene expression by binding to the 3’ untranslated region (3’UTR) of target mRNAs, impacting key cellular processes such as proliferation, differentiation, apoptosis, and migration. Dysregulation of miRNAs can disrupt the expression of oncogenes and tumor suppressor genes, contributing to cancer development. Among the various miRNAs studied, miR-152 has garnered attention for its role in urological malignancies. Several studies have indicated that dysregulation of miR-152 expression is significant in these cancers, warranting a comprehensive review of the evidence. This review focuses on the expression and function of miR-152 in prostate cancer, bladder cancer, and renal cell carcinoma, elucidating its mechanisms in cancer progression and exploring its potential as a therapeutic target and biomarker in urological malignancies.